Corn (Zea mayz L.) response to conservation tillage on four tropical soils. - Ureste, Jesús (2016)
Under the rainfed conditions of the central zonc of Veracruz Mexico, the res pon se of the maize crop to the conventional, reduced and zero tillage systems was evaluated in four tropical soils of different texture and drainagc degree. Plant population and grain yield were used as indicating variables. Economical aspects were measured by the Cost/Benefit relationship. The most uniform and highest plant population and grain yield were achieved in the fine and medium textured, well drained Fluvisols, showing no difference between these two soils or among the four tillage systems. In the coarse textured,excessively drained Luvisol, the plant population was higher with zero tillage than with the reduced and conventional tillage; however, the grain yield achieved with zero and reduced tillage was practically alike, but higher than that achieved with the conventional tillage. In the fine textured, poorly drained Venisol, the lowest graio yield was obtained with the four tillage systems, being higher for the conventional tillage system. Zero and reduced tillage reached the highest Cost/Benefit relationship in the Fluvisols and Luvisols. On the clay Vertisol soils, it is not economically feasible to produce corn with any of the studied tillage systems, unless the excess moisture in the soil is reduced.